Influence of Vertebrate Excreta on Attraction, Oviposition and Development of the Asian Tiger Mosquito, Aedes albopictus (Diptera: Culicidae) - R. Dulka T. Rajapaksha; Dona Pamoda W. Jayatunga; G. A. S. M. Ganehiarachchi (Insects, 2021)
Aedes albopictus is an important vector of dengue worldwide. Eliminating dengue in Sri Lanka depends entirely on controlling the vector and human-vector contact. Thus, studying the bionomics and behavior of Ae. albopictus is paramount. The objective of this study was to evaluate the effect of the excreta of cow, goat and pig on the attraction, oviposition and development of Ae. albopictus. Bioassay chambers determined the mosquito stimulatory response. Ovitraps determined Ae. albopictus oviposition preference to excreta singly, in combination and on fermentation. The excreta effect on larval development was also determined. The results revealed that Ae. albopictus gravid females were significantly attracted to goat excreta but were repelled by pig excreta. The oviposition preference was highest for cow excreta and lowest for pig excreta. For excreta combinations, the Cow+Goat combination increased the oviposition while the Pig+Goat combination reduced the oviposition. The oviposition preference of Ae. albopictus increased with the rate of fermentation. The pig excreta increased the Ae. albopictus larval mortality, larval and pupal duration and reduced adult fecundity, whereas the cow excreta positively affected all these aspects. Our findings additionally suggest that a high abundance of Ae. albopictus in rural areas of Sri Lanka may be due to its oviposition attraction and growth performance for vertebrate excreta.